2020
DOI: 10.1038/s41436-019-0729-1
|View full text |Cite
|
Sign up to set email alerts
|

Classification of variants of uncertain significance in BRCA1 and BRCA2 using personal and family history of cancer from individuals in a large hereditary cancer multigene panel testing cohort

Abstract: Purpose: Genetic testing of individuals often results in identification of genomic variants of unknown significance (VUS). Multiple lines of evidence are used to help determine the clinical significance of these variants. Methods: We analyzed~138,000 individuals tested by multigene panel testing (MGPT). We used logistic regression to predict carrier status based on personal and family history of cancer. This was applied to 4644 tested individuals carrying 2383 BRCA1/2 variants to calculate likelihood ratios in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Interestingly, in six samples, we detected VUSs. Previous studies have shown that co-segregation analysis and family history in a large cohort [ 44 ], as well as protein structure [ 45 ], in addition to the increasing number of functional studies, the development of computational prediction algorithms and database enlargement, allow VUSs to be reclassified as well [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in six samples, we detected VUSs. Previous studies have shown that co-segregation analysis and family history in a large cohort [ 44 ], as well as protein structure [ 45 ], in addition to the increasing number of functional studies, the development of computational prediction algorithms and database enlargement, allow VUSs to be reclassified as well [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Classification of VUS based on posterior probabilities from a Bayesian “system”, which by construction, requires specification of prior probabilities has been suggested by Plon et al 29 previously. Some recent BRCA VUS classification models have used the Align GVGD sequence conservation model to specify these prior probabilities 33 , 47 , 48 . In contrast, in the VarCall models we describe here, we specified a non-informative prior distribution on each variant’s function status.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge for BRCA and wider HRR gene testing is determining the clinical relevance of variants of uncertain significance (VUS) that are typically rarer missense mutations and also include intronic or exonic mutations that may alter RNA splicing. [43][44][45] The biological relevance of variants that lead to partial or 'leaky' splicing defects, particularly in BRCA2, that reduce full length transcript production are particularly hard to interpret. 46 The problem of VUS is even more pronounced for wider gene panel tests where the functional and clinical consequences of most individual genomic loci are not well characterised and individual mutations are not highly recurrent.…”
Section: Variants Of Uncertain Significancementioning
confidence: 99%